Dermoscopy of Cylindroma - Horacio Cabo; Florencia Pedrini; Emilia Cohen Sabban (Dermatology Research and Practice)
Background. Dermoscopy provides additional criteria for the diagnosis of nonpigmented skin lesions. Case Report. An 80-year-old woman presented with an isolated, firm, dome-shaped, erythematous nodule with surface telangiectasia on her forehead. Dermoscopy showed areas of background pink coloration with arborizing telangiectasia, blue dots/globules, and ulceration. Histologic analysis revealed features of cylindroma. Conclusion. Our case suggests that cylindromas may be added to the list of adnexal tumors mimicking BCC.